Coach succession and team performance: The impact of ability and timing -- Swedish ice hockey data - Salman, K.; Arnesson, L.; Shukur, G. (Journal of Quantitative Analysis in Sports, 2009)
The purpose of this study is to identify a function for the team performance for professional ice hockey teams in Sweden. In order to understand how team performance relates to key variables such as coaching ability and coaching experience and succession, the OLS (Ordinary Least Squares) and the more robust quantile regression techniques are used to estimate team performance for the ice hockey teams. Quarterly data for the period 1975-2006 is used for this purpose. The results have shown that coaching ability has a rather significant positive effect on team performance, and that managerial succession during the season is found to have a rather significant negative effect on team performance. The results also indicate a strong correlation between coaching ability and team performance. Moreover, the quantile regression approach provided a better understanding regarding the dynamics of the factors that affect performance and provided more interesting results than the OLS normally does.